Bioinformatics Analysis of the Actin Interactome - Yakov I. Mokin; Olga I. Povarova; Iuliia A. Antifeeva; Konstantin K. Turoverov; Irina M. Kuznetsova; Alexander V. Fonin (Proceedings)
Actin is a key protein of the muscle contraction system [...]